Sand mining, land degradation and rehabilitation in rural areas of South Africa : a case of Mentz Village, Limpopo Province - Malebana, Dineo Sarah (My University, 2021)
Sand mining has grown popular in South African rural communities due to its increasing demand for building purposes in and around the surrounding villages as well as a source of income to the rural communities. Sand is an indispensable natural resource of any society around the world. For instance, the government has to deal with the frequent sand mining environmental effects and implement various strategies on how to deal with these effects to protect the environment. Although the National Environmental Management Act (NEMA) 107 of 1998 regulates sand mining, the illegal and unregulated rural sand mining is causing land degradation, creating unpleasant appearances, causing vulnerability to floods and pointing out the need for rehabilitation. Given the circumstances surrounding the issue of illegal sand mining in rural communities, this research is aimed at investigating the impact of illegal or legal sand mining on the environment looking at the land degradation and the importance of rehabilitating the area after use in Mentz village. The main objective of this research was to explore how sand mining causes land degradation and examining the significance of rehabilitation in sand mining. The methodology of the study was carried out using both quantitative and qualitative research design in a form of questionnaire surveys, oral interviews and field observations to collect the data. The sample was composed of the general members of the community, the chief and the sand miners. For data analysis, the study used the Statistical Package for the Social Sciences (SPSS), IBM SPSS Statistics 25. The results indicated that sand mining causes 54.76% of the land degradation in South Africa. Furthermore, the research revealed that 30.95% of the land degradation was due to deforestation and 11.90% of Mentz land degradation was caused by overgrazing. Besides, an overwhelming 76.58% of the respondents agreed that land should be rehabilitated after sand mining processes.
Thesis (M. Dev. (Planning and Management)) -- University of Limpopo, 2021
Keywords: Sand mining; Rehabilitation; Environment; Land degradation; Sand and gravel mines and mining -- South Africa -- LImpopo; Land degradation; Soil degradation; Soil restoration